Positive electrode sheet, secondary battery, and electric device

By using composite positive electrode sheets in lithium-ion batteries and using the blending of the first and second positive electrode active materials, the problem of insufficient magnification tolerance boundary at low SOC and high SOC is solved, and better fast charging capability and service life are achieved.

CN119517934AActive Publication Date: 2025-02-25CONTEMPORARY AMPEREX TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411746058.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-02-06
Publication Date
2025-02-25
Estimated Expiration
2043-02-06

AI Technical Summary

Technical Problem

The existing lithium-ion battery positive electrode materials have poor rate tolerance boundaries at low SOCs, which affects fast charging capabilities and actual available capacity. At the same time, there is also a problem of insufficient rate tolerance boundaries at high SOCs.

Method used

The composite positive electrode sheet is adopted, including the first positive electrode active material LiaNibCocM1dM2eOfR′g and the second positive electrode active material Li1+xM3nMn1-yA′yP1-zEzO4. By blending these two materials, the ratio tolerance boundaries at high and low SOCs are broadened, the fast charging capacity is improved, and the high energy density and good cycling performance are combined.

Benefits of technology

Through the use of composite positive electrode materials, the battery's rate tolerance boundary at high and low SOCs is significantly broadened, the fast charging capability and battery service life are improved, while maintaining high energy density and good cycling performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119517934A_ABST
    Figure CN119517934A_ABST
Patent Text Reader

Abstract

The invention discloses a positive plate, a secondary battery and an electric device. Wherein the positive plate comprises a positive active material layer, the positive active material layer comprises a first positive active material and a second positive active material, the first positive active material comprises LiaNibCocM1dM2eOfR'g, and a is more than or equal to 0.75 and less than or equal to 1.2, 0lt; blt; 1, 0lt; clt; ct; 1, 0lt; dlt; 0 < = e < = 0.2, 1 < = f < = 2.5, 0 < = g < = 1, f + g < = 3, and M1 is Mn element and / or Al element; the second positive electrode active material comprises Li1 + xM3nMn1-yA'yP1-zEzO4, x is greater than or equal to-0.100 and less than or equal to 0.100, n is greater than or equal to 0 and less than or equal to 1.1, y is greater than or equal to 0.001 and less than or equal to 0.500, z is greater than or equal to 0 and less than or equal to 0.100, and A'comprises one or more elements of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge; the positive plate meets the formula: # imgabs0 #, wherein R is more than or equal to 0.1 and less than or equal to 1.2; w (Mn) is the mass fraction of Mn in the positive electrode active material layer; d is the thickness of the positive active material layer, and the unit is mm; t is the weight of the positive active material layer on the unit area of the positive plate, and the unit is g / cm < 2 >; r is the resistance of the positive plate at 25 DEG C, and the unit is omega.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with the application number 202380030554.3, the application date of February 6, 2023, and the invention title of "Positive Electrode Sheet, Secondary Battery, and Electrical Appliance". Technical Field

[0002] This application belongs to the technical field of batteries, and more specifically, relates to a positive electrode sheet, a secondary battery, and an electrical appliance. Background Art

[0003] Lithium-ion batteries have the characteristics of being green, environmentally friendly, high-energy, and low-carbon. They are not only used in energy storage power systems such as hydraulic, thermal, wind, and solar power stations, but also widely used in electric transportation such as electric bicycles, electric motorcycles, and electric vehicles, as well as in multiple fields such as military equipment and aerospace. With the development of current society, people's requirements for lithium-ion batteries are getting higher and higher, and fast charging performance and long service life have become important performance indicators for lithium batteries. Currently, ternary layered positive electrode materials are mostly selected for lithium-ion battery positive electrode materials, such as nickel cobalt manganese (NCM) system materials. However, conventional NCM system materials have a poor rate tolerance boundary at low voltages, which will affect the fast charging ability and actual available capacity of the battery. Summary of the Invention

[0004] In view of the technical problems existing in the background art, this application provides a positive electrode sheet, aiming to broaden the rate tolerance boundary of the positive electrode active material at high and low voltages, improve the fast charging ability, and at the same time obtain a long service life.

[0005] To achieve the above object, a first aspect of this application provides a positive electrode sheet, wherein the positive electrode sheet includes a positive electrode active material layer, and the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material.

[0006] The first positive electrode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, etc.; R′ includes one or more elements of N, F, S, Cl, etc.

[0007] The second positive electrode active material includes Li 1+x M 3n Mn1-y A′ y P 1-z E z O4, wherein -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤0.500, 0≤z≤0.100, M3 includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, and E includes one or more elements selected from the group consisting of B, Si, N, S, F, Cl and Br;

[0008] The positive electrode sheet satisfies:

[0009]

[0010] Where: 0.1≤R≤1.2;

[0011] w (Mn) is the mass fraction of Mn in the positive electrode active material layer;

[0012] d is the thickness of the positive electrode active material layer, in mm;

[0013] T is the weight of the positive electrode active material layer per unit area of ​​the positive electrode sheet, in g / cm 2 ;

[0014] R is the resistance of the positive electrode sheet at 25° C., in Ω.

[0015] Compared with the prior art, the positive electrode sheet of the first aspect of the present application has at least the following beneficial effects: (1) Li a Ni b Co c M 1d M 2e O f R′ g The positive electrode active material system has a poor rate tolerance margin at low SOC (state of charge, i.e., remaining capacity), and Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 has a poor rate tolerance margin at high SOC. By combining the two, the defects of the two systems can be compensated at the same time, and the rate tolerance margin at high and low SOC can be widened, thereby improving the fast charging capability; (2) By combining the positive electrode active material Li a Ni b Co c M 1d M 2e Of R′ g With positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 mixing can further make the battery have both high energy density and good cycle performance, thereby extending the service life; (3) Although the mechanism is not yet clear, by controlling the content of Mn element in the positive electrode active material layer, the thickness and surface density of the positive electrode active material layer, and the positive electrode sheet resistance to satisfy the above range, the fast charging capability, energy density and cycle performance can be guaranteed at the same time, and a fast charging positive electrode sheet with good cycle life can be obtained.

[0016] In some embodiments of the present application, Optionally, Among them, w (A′) is the mass fraction of A′ in the positive electrode active material layer, w (P) is the mass fraction of P in the positive electrode active material layer. By controlling it within the given range, we can further balance fast charging performance and long service life.

[0017] In some embodiments of the present application, 0.01≤w (A′) ≤0.05.

[0018] In some embodiments of the present application, the second positive electrode active material includes at least one of the following two positive electrode active materials: (i) 0.001≤y≤0.500, n=0, and the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4; (ii) 0.001≤y≤0.500, 0.9≤n≤1.1, the second positive electrode active material is Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4; Optionally, the second positive electrode active material is: (ii) Li 1+x Mn 1-y A′ y P 1-z E z O4.

[0019] In some embodiments of the present application, 0.032≤T≤0.043, optionally, 0.035≤T≤0.039. By controlling T within the given range, improved fast charging performance and cycle life, as well as higher energy density, can be further obtained.

[0020] In some embodiments of the present application, 0.11≤d≤0.16, optionally, 0.12≤d≤0.14. By controlling d within the given range, improved fast charging performance and cycle life, as well as higher energy density, can be further obtained.

[0021] In some embodiments of the present application, 0.1≤R≤1. By controlling R within the given range, the internal resistance of the electrode can be further reduced, and the fast charging performance and cycle performance can be improved.

[0022] In some embodiments of the present application, M1 is a Mn element.

[0023] In some embodiments of the present application, Optionally, Alternatively, By controlling Within the given range, on the basis of improving the fast charging capability, we can further take into account higher energy density and better cycle performance to extend the service life.

[0024] In some embodiments of the present application, the Dv50 particle size of the second positive electrode active material is 0.21 μm to 1.53 μm, optionally 0.32 μm to 1.4 μm, further optionally 0.41 μm to 1.25 μm, further optionally 0.38 μm to 1.1 μm, and further optionally 0.47 μm to 0.91 μm.

[0025] In some embodiments of the present application, the specific surface area of ​​the second positive electrode active material is 9.2 m 2 / g~23.6m 2 / g, optional 10.5m 2 / g~19.6m 2 / g, and can be selected as 12.0m 2 / g~16.2m 2 / g, 10.0m can also be selected 2 / g~21.5m 2 / g, and can be selected as 10.9m 2 / g~17.6m 2 / g.

[0026] In some embodiments of the present application, Optionally, By controlling the positive electrode sheet to meet the given conditions, the composite positive electrode can further have a better cycle life while having better power capability.

[0027] In some embodiments of the present application, the Dv50 particle size of the first positive electrode active material is 2.1 μm to 6.3 μm, and can be optionally 3.5 μm to 4.9 μm.

[0028] In some embodiments of the present application, the specific surface area of ​​the first positive electrode active material is 0.3 m 2 / g~1.2m 2 / g, optional 0.5m 2 / g~0.9m 2 / g.

[0029] In some embodiments of the present application, a first coating layer is provided on the surface of the first positive electrode active material. Optionally, the first coating layer includes one or more elements of Ti, Al, B, Nb, Zr, Si and W.

[0030] In some embodiments of the present application, the thickness of the first coating layer is 20 nm to 150 nm.

[0031] In some embodiments of the present application, a second coating layer is provided on the surface of the second positive electrode active material. Optionally, the second coating layer includes at least one of pyrophosphate, phosphate and carbon.

[0032] In some embodiments of the present application, the thickness of the second coating layer is 10 nm to 50 nm.

[0033] In some embodiments of the present application, in the second positive electrode active material, E includes one or more elements of B, Si, N and S.

[0034] In some embodiments of the present application, in the second positive electrode active material, A′ includes one or more elements of Fe, Ti, V, Ni, Co and Mg.

[0035] The second aspect of the present application provides a secondary battery, which includes: the positive electrode sheet of the first aspect of the present application.

[0036] The third aspect of the present application provides an electrical device, which includes: the positive electrode sheet of the first aspect of the present application, and / or the secondary battery described in the second aspect of the present application. DETAILED DESCRIPTION

[0037] The present application is further described below in conjunction with specific implementations. It should be understood that these specific implementations are only used to illustrate the present application and are not used to limit the scope of the present application.

[0038] Reference to "embodiments" in this application means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in this application may be combined with other embodiments.

[0039] The "range" disclosed in the present application is defined in the form of a lower limit and / or an upper limit, and a given range is defined by selecting a lower limit and / or an upper limit, and the selected lower limit and / or the rear upper limit define the boundary of a particular range. The range defined in this way can be inclusive or exclusive of the end value, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form an unambiguous range, and any lower limit can be combined with other lower limits to form an unambiguous range, and any upper limit can be combined with any other upper limit to form an unambiguous range. In addition, each individually disclosed point or single numerical value itself can be combined with any other point or single numerical value as a lower limit or upper limit or with other lower limits or upper limits to form an unambiguous range. For example, if a range of not more than 150 is listed for a specific parameter, it is also expected that 10 to 140 and 20 to 120 etc. meet the range of not more than 150. In addition, if the minimum range values ​​2.1 and 3.5 are listed, and if the maximum range values ​​4.9 and 6.3 are listed, the following ranges are all expected: 2.1-6.3, 2.1-4.9, 3.5-6.3, and 3.5-4.9. In this application, unless otherwise specified, a numerical range such as "10-50" represents an abbreviation of any real number combination between 10 and 50, where 10 and 50 are both real numbers. For example, the numerical range "20-30" means that all real numbers between "20-30" have been fully listed in this document, and "20-30" is just an abbreviation of these numerical combinations.

[0040] If not otherwise specified, all embodiments and optional embodiments of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0041] Unless otherwise specified, all technical features and optional technical features of the present application may be combined with each other to form new technical solutions, and such technical solutions should be deemed to be included in the disclosure of the present application.

[0042] If there is no special explanation, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S1 and S2, which means that the method may include steps S1 and S2 performed sequentially, or may include steps S2 and S1 performed sequentially. For example, the method may also include step S3, which means that step S3 may be added to the method in any order. For example, the method may include steps S1, S2 and S3, or may include steps S1, S3 and S2, or may include steps S3, S1 and S2, etc.

[0043] Unless otherwise specified, the terms "include" and "comprising" mentioned in this application may be open-ended or closed-ended. For example, the terms "include" and "comprising" may mean that other components not listed may also be included or contained, or may only include or contain the listed components. In addition, in this application, the terms "plurality" and "multiple" refer to two or more.

[0044] If there is no special explanation, in this application, the term "and / or" is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0045] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as those commonly understood by technicians in the technical field of this application; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and any variations thereof are intended to cover non-exclusive inclusions. Unless otherwise specified, the terms used in this application have the well-known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0046] At present, fast charging performance and long service life have become important performance indicators of lithium batteries. Currently, ternary layered cathode active materials (such as NCM) are mostly used to prepare cathode sheets. However, with the increase in the number of cycles and the extension of discharge time for the cathode materials in this system, problems such as increased battery internal resistance and increased electrode polarization will occur. As a result, the discharge voltage reaches the cut-off voltage in advance, and there is a tendency for the discharge voltage to drop steeply at the end of the discharge curve, leading to early termination of discharge and affecting the actual available capacity of the battery. That is, the cathode materials in this system have a poor rate tolerance boundary at low SOC, affecting the fast charging and cycling performance of the battery. In addition, although ternary layered cathode active materials (such as NCM) have a relatively high energy density, their cycle life and fast charging performance are not excellent.

[0047] In view of this, a first aspect of the present application provides a cathode sheet, wherein the cathode sheet includes a cathode active material layer, the cathode active material layer includes a first cathode active material and a second cathode active material, and the first cathode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements selected from Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb; R′ includes one or more elements selected from N, F, S, Cl; the second cathode active material includes Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, where -0.100 ≤ x ≤ 0.100, 0 ≤ n ≤ 1.1, 0.001 ≤ y ≤ 0.500, 0 ≤ z ≤ 0.100, M3 includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, E includes one or more elements selected from B, Si, N, S, F, Cl and Br; the cathode sheet satisfies:

[0048]

[0049] Where: 0.1 ≤ R ≤ 1.2; w (Mn)is the mass fraction of Mn in the positive electrode active material layer; d is the thickness of the positive electrode active material layer, in mm; T is the weight of the positive electrode active material layer per unit area of ​​the positive electrode sheet, in g / cm 2 ; R is the resistance of the positive electrode sheet at 25° C., in Ω. Wherein, the dimension of “mass fraction” described in this application is 1.

[0050] Layered cathode active material system Li a Ni b Co c M 1d M 2e O f R′ g The rate tolerance margin is poor at low SOC, and the positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 has a low-voltage discharge platform (generally no more than 3.5V) at the end of discharge. By mixing it with the above-mentioned layered positive electrode active material, Li 1+x M 3n Mn 1-y A′ y P 1-z E z The discharge platform of O4 at low voltage makes the overall discharge curve of the mixed composite positive electrode active material have a discharge platform near the end. When the battery discharges to this platform, since the battery voltage changes less with the capacity, it is equivalent to a certain degree of constant voltage discharge of the layered positive electrode active material, thereby alleviating the polarization effect in the previous discharge process at low voltage and improving the actual available capacity; and the positive electrode active material system Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 is also limited by the problem of poor rate tolerance margin at high SOC. a Ni b Co c M 1d M 2e O f R′ g Mixed use can make up for the defects of the two systems at the same time, broaden the rate tolerance boundary at high and low SOC, thereby improving the fast charging capability and taking into account the cycle performance; in addition, the positive electrode active material Li a Ni b Co c M1d M 2e O f R′ g The energy density is higher, and the positive electrode active material Li 1+ x M 3n Mn 1-y A′ y P 1-z E z O4 has higher cycle performance and safety. By mixing the two, the electrode can further have both higher energy density and better cycle performance, extending the service life. Moreover, the positive electrode active material Li 1+x M 3n Mn 1- y A′ y P 1-z E z The lattice shrinkage rate of O4 during the charge and discharge process is relatively large. Mixing the positive electrode active materials of the two systems is also beneficial to further match the expansion of the battery negative electrode sheet and improve the long-term performance of the battery.

[0051] Furthermore, Li a Ni b Co c M 1d M 2e O f R′ g With Li 1+x M 3n Mn 1-y A′ y P 1-z E z After O4 is mixed, by controlling the content of Mn element in the positive electrode active material layer, the thickness and surface density of the positive electrode active material layer, and the positive electrode sheet resistance to meet the above range, the fast charging capability, energy density and cycle performance can be guaranteed at the same time, and a fast charging positive electrode sheet with a good cycle life can be obtained. The reasons for the analysis may include but are not limited to: the coating quality of the positive electrode active material will affect the Li a Ni b Co c M 1d M 2e O f R′ g With Li 1+ x M 3n Mn 1-y A′ y P 1-z E z The mixing effect of O4, for example, when the coating quality of the positive electrode active material layer is too low, the polarization of the electrode will be significantly improved.a Ni b Co c M 1d M 2e O f R′ g Mixed with Li 1+x M 3n Mn 1-y A′ y P 1-z E z The improvement of O4 is not significant, and when the coating quality of the active material layer is too high, the polarization of the pole piece will increase to a greater extent than that of the mixed Li 1+ x M 3n Mn 1-y A′ y P 1-z E z O4's improvement effect; secondly, the surface density of the positive electrode active material layer is related to its thickness and compaction density. When the surface density is determined, if the thickness of the positive electrode active material layer is too small, it means that the coating on the positive electrode sheet is too thin or the compaction density is too large. The former affects the energy density, and the latter affects the infiltration of the electrolyte into the electrode sheet, which will deteriorate the cycle performance. If the thickness is too large, it means that the coating on the positive electrode sheet is too thick or the compaction density is too small. The former will increase the polarization of the electrode sheet and deteriorate the battery performance, and the latter will increase the contact resistance between particles in the electrode sheet and deteriorate the battery performance. In addition, if the resistance R of the positive electrode sheet is too high, it will also affect the power and cycle performance.

[0052] In the present application, the mass fraction w of each element (such as A' element, Mn element) in the positive electrode active material layer is (A′)The mass of the positive electrode active material layer and the mass of the A' element in the positive electrode active material layer can be measured separately and then calculated, wherein the mass of the positive electrode active material layer can be obtained by disassembling and weighing (accurate to 0.0001g), and the mass of the A' element in the positive electrode active material layer can be obtained in combination with ICP testing. For example, it can be performed as follows: take about 0.4g (accurate to 0.0001g) of dry positive electrode sheet or 0.1g (accurate to 0.0001g) of wet positive electrode sheet in a 30ml digestion tank, retain one digestion tank without sample as a blank sample, move the digestion tank containing the positive electrode sheet sample into a fume hood and add 12ml of reverse aqua regia. When adding reverse aqua regia, add it along the inner wall of the digestion tank so that the residual sample on the inner wall is washed into the bottom of the tank, and then install the top cover, insulation sleeve, gasket, microwave digestion device, nut in sequence, tighten the nut with a wrench, then turn on the microwave digester, and turn on the microwave digestion The fiber optic sensor in the instrument is inserted into the bottom of the previously assembled digestion tank containing the sample, and the digestion tank is placed in the microwave digestion instrument in a balanced manner to start digestion (the digestion program is to heat up to 120℃ for 6 minutes and hold for 8 minutes, heat up to 160℃ for 5 minutes and hold for 8 minutes, and heat up to 180℃ for 5 minutes and hold for 5 minutes). After the digestion is completed, it is cooled to room temperature and taken out. The digestion tank is placed in a fume hood, and the nut is slowly unscrewed to release the air. The previously installed parts are removed one by one, and the solution in the digestion tank is transferred to a 100ml volumetric flask through a funnel (filter paper is required). The digestion tank is then rinsed with ultrapure water, and the rinse liquid is also transferred to the volumetric flask. 10ml of ultrapure water is used for each rinse. The solution in the 100ml volumetric flask is shaken evenly, and 1ml of the shaken solution is taken with a pipette and added to another 100ml volumetric flask, and then ultrapure water is added to make up the volume (the total solution reaches 100ml), and finally the sample solution is tested using ICP-OES. Among them, when preparing reverse aqua regia, 1000ml of ultrapure water can be poured into a 2500ml glass bottle, and then 750ml of concentrated nitric acid and 250ml of concentrated hydrochloric acid are added in sequence, stirred evenly and set aside. The concentrated nitric acid can be purchased from the market in the form of a concentrated nitric acid solution with a mass fraction of 68%, and the concentrated hydrochloric acid can be purchased from the market in the form of a concentrated hydrochloric acid with a mass fraction of 68%, or hydrogen chloride gas and ultrapure water can be added to ultrapure water in a mass ratio of 68% and 32% respectively, and the required concentrated hydrochloric acid can be obtained after complete dissolution.

[0053] In the present application, the coating mass T of the positive electrode active material layer can be tested by a weighing method, and can be specifically obtained by weighing the positive electrode active material layer within a fixed area (accurate to 0.0001 g).

[0054] In this application, the resistance of the positive electrode sheet can be tested at room temperature using a BER1300 film resistor. The test steps can be as follows: (1) Prepare the electrode sheet into a round sheet with a diameter of 22 mm; (2) Place the prepared round sheet on the test platform of the BER1300 instrument; (3) Adjust the machine test pressure to 0.4 tons and the test time to 10 s, and then start the test. The obtained resistance value is the film resistance.

[0055] In this application, the thickness d of the active material layer of the positive electrode sheet can be tested by referring to the following method: Take a 1×2 cm area at the center of the electrode sheet, transfer it under a vacuum transfer device or in an inert gas protection environment, make a cross-section at low temperature using an argon ion beam milling (CP) device, cut it, attach it to the cross-section sample stage with conductive tape, and transfer it to the SEM vacuum chamber for sample observation. Adjust the appropriate parameters until the cross-sectional morphology can be clearly observed. Use the scanning electron microscope software to mark the thickness of the active material layer, mark 3 regions respectively, and take the average value as the thickness of the active material layer. 2 area, transfer it under a vacuum transfer device or in an inert gas protection environment, make a cross-section at low temperature using an argon ion beam milling (CP) device, cut it, attach it to the cross-section sample stage with conductive tape, and transfer it to the SEM vacuum chamber for sample observation. Adjust the appropriate parameters until the cross-sectional morphology can be clearly observed. Use the scanning electron microscope software to mark the thickness of the active material layer, mark 3 regions respectively, and take the average value as the thickness of the active material layer.

[0056] Furthermore, on the basis of meeting the above conditions, the positive electrode sheet of this application can further control the element mass fraction, the selection of the positive electrode active material, the electrode sheet resistance, the surface density and thickness of the positive electrode active material layer, etc. to further improve the performance of the positive electrode sheet. That is, on the basis of meeting the above conditions, one or more of the following conditions can also be optionally met.

[0057] In some embodiments of this application, part of the first positive electrode active material can be Li a Ni b Co c M 1d M 2e O f R′ g , or all of it can be Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements among Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, and R′ includes one or more elements among N, F, S, Cl. Optionally, 0.5 ≤ b < 1, 0 < c ≤ 0.5, 0 < d ≤ 0.5, so that the positive electrode active material Li a Ni b Co c M1d M 2e O f R′ g Meeting the above-given range conditions is more conducive to making the electrode and the battery have higher energy density, good cycle performance and longer cycle life. The positive electrode active material Li a Ni b Co c M 1d M 2e O f R′ g In the example of the nickel-cobalt-manganese ternary positive electrode active material (ie, NCM) system, increasing the nickel content can increase the volume energy density of the positive electrode material; increasing the manganese content can reduce the material cost, improve the safety and structural stability of the material, and improve the cycle performance, but too high a manganese content will destroy the layered structure of the material and reduce the specific capacity of the material; cobalt can stabilize the layered structure of the material and improve the cycle and rate performance of the material, but too high a cobalt content will lead to a decrease in the actual capacity. By making the nickel-cobalt-manganese content meet the above-given range conditions, it is beneficial for the electrode and the battery to have a higher energy density, good rate performance and cycle performance. Optionally, M1 can be a Mn element, and the first positive electrode active material can be a positive electrode active material of the NCM system, in which case its general formula can be Li a Ni b Co c Mn d M 2e O f R′ g , for example, it can be a nickel-cobalt-manganese ternary layered positive electrode active material.

[0058] In some embodiments of the present application, the second positive electrode active material may be partially Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, or all Li 1+x M 3n Mn 1-y A′ y P 1-z E zO4, wherein, -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤1, 0≤z≤0.100, M3 includes one or more elements selected from Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, and E includes one or more elements selected from B, Si, N, S, F, Cl and Br. Doping at least one of the lithium site, manganese site and phosphorus site can help improve the performance of the positive electrode active material, for example, improve the interface performance, reduce the interface side reaction with the electrolyte, reduce the concentration of anti-site defects, improve the material kinetic performance and gram capacity, etc. At the same time, by regulating the doping element at the manganese site, the particle morphology can also be improved and the compaction density can be increased. Specifically, the second positive electrode active material mentioned above is doped during the charge and discharge process. The lattice volume change rate in the process is larger than that of the first positive electrode active material, which can better match the volume expansion of the negative electrode during the charging process. However, if the lattice volume change rate of the positive electrode material is too high, it is not conducive to the transmission of lithium ions. The element A' doped at the manganese position is selected from the above elements to help appropriately reduce the lattice change rate of the material during the lithium insertion and extraction process, improve the structural stability of the positive electrode material, reduce the dissolution of the manganese position element and reduce the oxygen activity on the surface of the particles, thereby increasing the gram capacity of the material, and reducing the interface side reaction between the material and the electrolyte during use, thereby improving the cycle performance of the material, etc.; the element E doped at the phosphorus position is selected from the above elements to help change the difficulty of the Mn-O bond length change, thereby improving the electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the rate performance and fast charging performance; similarly, the element M3 doped at the lithium position is selected from the above elements to help improve the lattice change rate of the material and maintain the capacity of the material. If the value of x is too small, the lithium content of the entire core system will be reduced, affecting the gram capacity of the material. The y value will limit the total amount of all doping elements, affecting the manganese content in the system and the voltage platform of the material. The E element is doped at the position of phosphorus. Since the PO tetrahedron is relatively stable, a large z value will affect the stability of the material. When x, y and z are selected from the above range, the positive electrode active material can have better performance. In addition, the selection of the above doping elements and x, n, y, z values ​​can also make Li 1+x M 3n Mn 1-y A′ y P 1-z E zO4 maintains electrical neutrality, and maintaining electrical neutrality is conducive to minimizing defects and impurities in the positive electrode active material. Taking the positive electrode active material of the lithium manganese phosphate system as an example, if there is an excess of transition metal (such as manganese), since the structure of the material system itself is relatively stable, the excess transition metal is likely to precipitate in the form of a single substance, or form an impurity phase inside the lattice. Maintaining electrical neutrality can minimize such impurities; in addition, making the system electrically neutral can also produce lithium vacancies in the positive electrode active material in some cases, thereby making the kinetic performance of the positive electrode active material better. Compared with existing materials such as lithium manganese phosphate, lithium iron phosphate, and lithium manganese iron phosphate that can be applied to high voltage systems, it is more conducive to obtaining better cycle performance and high temperature stability, as well as larger gram capacity and larger compaction density. It can be understood that in the "manganese position" doping described in this application, the manganese position only represents the positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1- z E z The position of the manganese element or the A' element in the O4 lattice does not mean that there must be a manganese element in the manganese position. The manganese element on the manganese position can be partially or completely replaced by the A' element. For example, when the y value is 1, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 does not contain manganese. For example, in this case, the manganese may be replaced by iron or iron and other doping elements.

[0059] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z In O4, E may include one or more elements of B, Si, N and S. By selecting the phosphorus-doped element E from the given range, it can further help to change the difficulty of changing the Mn-O bond length, thereby improving electronic conductivity and reducing the lithium ion migration barrier, promoting lithium ion migration, and improving the material's rate performance and fast charging performance.

[0060] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E zIn O4, A' may include one or more elements of Fe, Ti, V and Mg. Optionally, A' may be Fe; further optionally, A' may be at least two elements selected from Fe, Ti, V and Mg; further optionally, A' may be Fe and one or more elements selected from Ti, V and Mg. By selecting the manganese-doped element A' from the given range, the structural stability, gram capacity, cycle performance, rate performance, etc. of the positive electrode material can be further improved, and a positive electrode sheet with both good cycle life and fast charging performance can be obtained.

[0061] In some embodiments of the present application, the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z In O4, doping can be performed at the manganese and phosphorus positions at the same time, which can not only effectively reduce the dissolution of manganese elements, thereby reducing the manganese ions that migrate to the negative electrode, reducing the electrolyte consumed due to the decomposition of the SEI film, and improving the cycle performance and safety performance, but also promote the adjustment of the Mn-O bond, reduce the lithium ion migration barrier, promote lithium ion migration, and improve the rate performance and fast charging capability. Optionally, doping can also be performed at the lithium, manganese and phosphorus positions at the same time, thereby further obtaining significantly improved rate performance, improved cycle performance and / or high temperature stability.

[0062] In this application, the chemical formula of the first positive electrode active material is Li a Ni b Co c M 1d M 2e O f R′ g and the chemical formula of the second positive electrode active material Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, unless otherwise specified, when a doping site has two or more elements, the numerical range of the stoichiometric number of the elements of the corresponding doping site in the chemical formula is limited not only to the stoichiometric number of each element as the site, but also to the sum of the stoichiometric numbers of the elements as the site. 1+x M 3n Mn 1-y A′ y P 1-z E z Taking the chemical formula of O4 as an example, when A1′ is two or more elements A1′, A2′…A n', A1', A2'...A n 'The respective stoichiometric numbers y1, y2...y n Each of them must fall within the numerical range of y specified in this application, and y1, y2...y n Similarly, for the case where M3 or E is two or more elements, the numerical range of the stoichiometric number of M3 and E defined in this application also has the above meaning.

[0063] In some embodiments of the present application, The value range of is 0.002 to 0.2, for example, it can be 0.0025, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11, 0.12, 0.13, 0.14, 0.15, 0.16, 0.17, 0.18, 0.19, etc., or within any range of the above values. Optionally, The value range of can be 0.07-0.1, then 0.07-0.092, then 0.07-0.9, and then 0.07-0.8. If the value of is within the given range, a fast-charging positive electrode sheet with a better cycle life can be further obtained.

[0064] In some embodiments of the present application, w (A′) is the mass fraction of A′ in the positive electrode active material layer, w (P) is the mass fraction of phosphorus element P in the positive electrode active material layer, for example, The value of can be 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, etc., or any range of the above values. a Ni b Co c M 1d M 2e O f R′ g With Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 doping is beneficial to improve the power capacity at lower voltages and the cycle performance of the composite positive electrode. As the mixing ratio of the two changes, the power capacity at low and high voltages and the cycle performance of the composite positive electrode will also change. For example, when Li 1+x M 3n Mn 1-y A′y P 1-z E z When the O4 mixing ratio is too high, it will affect the power capacity at higher voltages, thereby deteriorating the power capacity of the composite positive electrode. Controlling within the given range is beneficial to making Li a Ni b Co c M 1d M 2e O f R′ g With Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4 has a suitable blending ratio, so that the composite positive electrode has better power capacity and cycle performance, and can better balance fast charging performance and long service life. By Controlling within the given range can further optimize Li a Ni b Co c M 1d M 2e O f R′ g and Li 1+x M 3n Mn 1-y A′ y P 1-z E z The mixing ratio of O4 is adjusted to obtain a fast-charging positive electrode sheet with a better cycle life.

[0065] In some embodiments of the present application, the mass fraction of the A' element in the positive electrode active material layer satisfies: 0.01≤w (A′) ≤0.05, for example, w (A′) The value of can be 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045, etc., or within any range of the above-mentioned values, in the second positive electrode active material, increasing the content of the A' element helps to improve the cycle performance, but too high a content of the A' element will damage the energy density. In the present application, by further controlling the mass fraction of A' in the positive electrode active material layer within the given range, the cycle performance and high energy density can be further taken into account on the basis of improving the fast charging performance of the positive electrode sheet, thereby extending the service life.

[0066] In some embodiments of the present application, the second positive electrode active material may include a lithium manganese phosphate system, a lithium iron phosphate system, a lithium manganese iron phosphate system, etc., all of which conform to the above general formula Li 1+x M 3n Mn1-y A′ y P 1-z E z One or more of the positive electrode active materials of O4, for example, the second positive electrode active material may include a positive electrode active material that satisfies at least one of the following two conditions: (i) 0.001≤y≤0.500, n=0, in which case the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4, that is, it can be lithium manganese phosphate doped with at least manganese position, wherein, in the present application, the modification of lithium manganese phosphate is conducive to achieving significantly reduced dissolution of manganese position elements and reduced lattice change rate, and its use in secondary batteries is more conducive to improving the battery's cycle performance, rate performance, safety performance and increasing the battery's capacity. For example, by doping specific elements in specific amounts at the lithium position, manganese position, and phosphorus position of the compound LiMnPO4, it is conducive to obtaining improved rate performance, while reducing the dissolution of Mn and Mn-doped elements, obtaining improved cycle performance and / or high temperature stability, and the gram capacity and compaction density of the positive electrode active material can also be improved. As a specific example, Li 1+x Mn 1-y A′ y P 1-z E z O4 may include Li 1+x Mn 1-y Fe y P 1-z E z O4, compared with lithium iron phosphate, lithium manganese iron phosphate has a higher voltage platform and a higher energy density when the specific capacity is the same; (ii) 0.001≤y≤0.500, 0.9≤n≤1.1, in this case, the second positive electrode active material is Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, for the second positive electrode active material of the lithium manganese phosphate system, considering that the y value will limit the total amount of all doping elements, if y is too small, that is, the doping amount is too little, the doping element will not work, if y exceeds 0.5, it will lead to less Mn content in the system, affecting the voltage platform of the material, the value range of y can be selected from 0.001 to 0.500, and then from 0.25 to 0.5. It should be noted that the chemical formula Li involved in the above two conditions 1+x Mn 1-y A′ y P 1-z E z O4 and Li 1+xM 3n Mn 1-y A′ y P 1-z E z In O4, the stoichiometric numbers of elements at the same site can be the same or different, but they all satisfy the chemical formula Li 1+x M 3n Mn 1-y A′ y P 1-z E z The numerical range defined for the stoichiometric number of each element in O4.

[0067] As a specific example, the second positive electrode active material may include a positive electrode active material that satisfies the following conditions: 0.001≤y≤0.500, n=0, and the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z Alternatively, the second positive electrode active material may include only Li 1+x Mn 1-y A′ y P 1-z E z Alternatively, A′ may include Fe element, for example, may be only Fe element.

[0068] In some embodiments of the present application, the weight T (in g / cm2) of the positive electrode active material layer per unit area of ​​the positive electrode sheet is 2 ) satisfies: 0.032≤T≤0.043, for example, T can be 0.033, 0.034, 0.035, 0.036, 0.037, 0.038, 0.039, 0.040, 0.041, 0.042, etc., or within any range of the above values. The coating quality of the positive electrode active material layer not only affects the polarization of the electrode sheet, but also affects the energy density of the electrode sheet. Under the premise of satisfying the relationship between the content of the A′ element in the positive electrode active material layer, the thickness and surface density of the positive electrode active material layer, and the resistance of the positive electrode sheet, the present application further controls the surface density T of the positive electrode active material layer within the given range, thereby further obtaining improved fast charging performance and cycle life, as well as higher energy density and extended service life. Optionally, 0.035≤T≤0.039, further controlling T within the given range can further enable the positive electrode sheet to have both good fast charging capability and long service life.

[0069] In some embodiments of the present application, the thickness d (unit: mm) of the positive electrode active material layer satisfies: 0.11 ≤ d ≤ 0.16. For example, the value of d can be 0.115, 0.12, 0.125, 0.13, 0.135, 0.14, 0.145, 0.15, 0.155, etc., or within any range of any of the above values. The thickness of the positive electrode active material layer not only affects the energy density of the battery, but also affects its cycle performance and fast charging performance. On the premise of satisfying the relationship formula of the content of element A' in the positive electrode active material layer, the thickness and surface density of the positive electrode active material layer, and the positive electrode sheet resistance, by further controlling the thickness d of the positive electrode active material layer within the given range, it is possible to further simultaneously obtain improved fast charging performance and cycle life, as well as a higher energy density, and extend the service life. Optionally, 0.12 ≤ d ≤ 0.14. Further controlling d within the given range can further enable the positive electrode sheet to have both good fast charging ability and long service life.

[0070] In some embodiments of the present application, the resistance R (unit: Ω) of the positive electrode sheet satisfies: 0 < R ≤ 1.2. For example, the value of R can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, etc., or within any range of any of the above values. Considering that too high a resistance of the positive electrode sheet will also affect the power performance and cycle performance of the battery, by controlling the value range of R within the given range, it is further beneficial to enable the electrode sheet to have good fast charging performance and cycle performance. Optionally, 0.1 ≤ R ≤ 1. By further controlling the value range of R within the given range, it is possible to further reduce the internal resistance of the electrode sheet and improve the fast charging performance and cycle performance.

[0071] In some embodiments of the present application, the mass fractions of Mn element and A' element in the positive electrode active material layer may also satisfy the following conditions: w (Mn) is the mass fraction of manganese in the positive electrode active material layer. For example The value of can be 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, etc., or within any range of any of the above values. The content of element A' in the second positive electrode active material affects the voltage platform and cycle performance of the material. A high content of element A' helps to improve the cycle performance, but there will be an obvious loss in the platform voltage, which is not conducive to the energy density of the battery. For example, as a specific example, when the manganese site contains both manganese element and iron element at the same time, a higher manganese-iron ratio can increase the voltage platform, which is beneficial to improving the energy density of the battery. However, when the manganese-iron ratio is too high, a large amount of trivalent manganese in the delithiated state may damage the solid solution structure, reduce the specific capacity and cycle capacity retention rate of the material, resulting in poor cycle performance and affecting the life of the positive electrode. In the present application, by controlling The value of is within the given range, so that the second positive electrode active material can have a suitable A' element content range, thereby further taking into account higher energy density and better cycle performance on the basis of improving fast charging capability, and extending service life. Optionally, Alternatively, This can further achieve high energy density, as well as improved fast charging performance and long service life.

[0072] As a specific example, the first positive electrode active material may be a positive electrode active material Li a Ni b Co c Mn d M 2e O f R′ g , such as Li a Ni b Co c Mn d O f R′ g The second positive electrode active material may be Li 1+x Mn 1-y A′ y P 1-z E z O4 (0.001≤y≤0.500), such as Li 1+x Mn 1-y Fe y P 1-z E z O4, at this time The value range of can be 3 to 20, can be 4 to 18, and can be 5 to 17; further, The value range of can be 0.27~1.63, and can be selected as 0.72~1.26; further, w (A′) The value of can be 0.01 to 0.05. In the present application, by making the positive electrode sheet meet the given conditions, the improved fast charging performance, cycle performance and long service life can be further obtained.

[0073] In some embodiments of the present application, the positive electrode sheet can simultaneously meet the following two conditions: Optionally, The content of Mn and A' in the positive electrode active material layer, especially in the second positive electrode active material, will directly or indirectly affect the fast charging capability and cycle life of the composite positive electrode. The change in the value of The value range of will also change accordingly. and When the values ​​of satisfy the given range at the same time, the composite positive electrode can further have a better power capability and a better cycle life.

[0074] In some embodiments of the present application, the Dv50 particle size of the first positive electrode active material is 2.1 μm to 6.3 μm, for example, it can be 2.4 μm, 2.7 μm, 3.0 μm, 3.3 μm, 3.6 μm, 3.9 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5.1 μm, 5.4 μm, 5.7 μm, 6.0 μm, etc., or within any range of the above values. The Dv50 of the first positive electrode active material refers to the particle size corresponding to the cumulative volume distribution percentage of the first positive electrode active material reaching 50%. In the present application, the Dv50 particle size of the first positive electrode active material can be measured by laser diffraction particle size analysis, for example, with reference to the standard GB / T 19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000) for measurement. In this application, by controlling the Dv50 particle size of the first positive electrode active material within the given range, it is not only beneficial to prevent it from breaking or pulverizing during the charge and discharge process, thereby reducing capacity loss, but also can shorten the diffusion path of active ions and increase the conduction rate of electrons, which is beneficial to improving cycle performance; at the same time, it can also make the active material have suitable active sites, reduce or avoid the increase of side reactions of the material during the cycle due to the large number of active sites when the particle size is too small, which has a greater negative impact on the cycle performance, and the small number of active sites when the particle size is too large, which has a greater negative impact on the power performance. Optionally, the Dv50 particle size of the first positive electrode active material can be 3.5μm to 4.9μm, which can further take into account high energy density, good power performance and cycle performance, and improve fast charging capability and service life.

[0075] In some embodiments of the present application, the Dv50 particle size of the second positive electrode active material may be 0.21 μm to 1.53 μm, for example, 0.25 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, etc., or within any range of the above values. The Dv50 of the second positive electrode active material refers to the particle size corresponding to the cumulative volume distribution percentage of the second positive electrode active material reaching 50%. In the present application, the Dv50 particle size of the second positive electrode active material can be measured by laser diffraction particle size analysis, for example, with reference to the standard GB / T 19077-2016, using a laser particle size analyzer (such as Malvern Master Size 3000) for measurement. In this application, by controlling the Dv50 particle size of the second positive electrode active material within the given range, it is not only beneficial to prevent it from breaking or pulverizing during the charge and discharge process, thereby reducing capacity loss, but also can shorten the diffusion path of active ions and increase the conduction rate of electrons, which is beneficial to improving the cycle performance, and at the same time, it can also make the active material have suitable active sites, while taking into account both the cycle performance and the power performance; and, controlling the Dv50 particle size of the second positive electrode active material within the given range is also beneficial to match the Dv50 particle size range of the first positive electrode active material to achieve the expected compaction density, and avoid large gaps between the positive electrode active material particles. Optionally, the Dv50 particle size of the second positive electrode active material can be 0.5μm to 0.9μm, thereby further taking into account high energy density, good power performance and cycle performance, and improving fast charging capability and service life.

[0076] In some embodiments of the present application, the specific surface area of ​​the first positive electrode active material may be 0.3 m 2 / g~1.2m 2 / g, for example, 0.4m 2 / g, 0.5m 2 / g, 0.6m 2 / g, 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, or within any range of the above values; Optionally, the specific surface area of ​​the first positive electrode active material can be 0.5m 2 / g~0.9m 2 / g. Further, the specific surface area of ​​the second positive electrode active material can be 9.2m 2 / g~23.6m 2 / g, for example, 10m 2 / g, 11m2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, or within any range of the above values; Optionally, the specific surface area of ​​the second positive electrode active material is 10.5m 2 / g~19.6m 2 / g, and can be selected as 12.0m 2 / g~16.2m 2 / g, 10.0m can also be selected 2 / g~21.5m 2 / g, and can be selected as 10.9m 2 / g~17.6m 2 / g. In the present application, the specific surface areas of the first and second positive electrode active materials can be determined by conventional methods in the art, such as nitrogen physical adsorption. The increase in specific surface area helps to increase the active sites of the positive electrode active material, so that the material has better power performance, but these increased active sites will also increase the side reactions of the positive electrode active material during the cycle, thereby causing the material cycle performance to decay. In the present application, by controlling the specific surface areas of the first positive electrode active material and the second positive electrode active material within the given range, better power performance and cycle life can be further obtained, and the fast charging capability and service life can be improved.

[0077] As a specific example, when the positive electrode active material layer satisfy When the second positive electrode active material has a Dv50 particle size of 0.21 μm to 1.53 μm, and a specific surface area of ​​9.2 m 2 / g~23.6m 2 / g; further, when satisfy When the Dv50 particle size of the second positive electrode active material can be 0.38 μm to 1.10 μm, and can be 0.47 μm to 0.91 μm, the specific surface area of ​​the second positive electrode active material can be 10.5 m 2 / g~19.9m 2 / g, optional 12.0m 2 / g~16.2m 2 / g; further, when satisfy When the Dv50 particle size of the second positive electrode active material can be 0.32 μm to 1.40 μm, and can be 0.41 μm to 1.25 μm, the specific surface area of ​​the second positive electrode active material can be 10.0 m 2 / g~21.5m 2 / g, optional 10.9m 2 / g~17.6m 2 / g. The changes in Dv50 particle size and specific surface area in the second positive electrode active material will affect the power performance and cycle life of the material, and different The corresponding optimal Dv50 particle size and specific surface area ranges are also different. The Dv50 particle size and specific surface area of ​​the second positive electrode active material meet the above-given range conditions, which can further enable the composite positive electrode to have a better cycle life while having a better power capability.

[0078] In some embodiments of the present application, the surface of the first positive electrode active material may be provided with a first coating layer, and optionally, the first coating layer may include one or more elements of Ti, Al, B, Nb, Zr, Si and W. Providing a coating layer on the surface of the positive electrode active material can not only prevent the positive electrode active material from contacting with the electrolyte, thereby reducing the side reaction between the positive electrode active material and the electrolyte, but also improve the stability of the structure of the positive electrode active material, thereby improving the cycle stability and safety of the material; in addition, the above elements in the first coating layer can be provided in the form of oxides (such as Al2O3, ZrO2, TiO2, Nb2O3, etc.), or in the form of lithium compounds, etc., so that the first coating layer contains the above-given element range, which can improve the material surface ion conductivity, improve the material rate performance and gram capacity, stabilize the material structure, avoid direct contact between the material and the electrolyte, and improve the cycle performance.

[0079] In some embodiments of the present application, the thickness of the first coating layer can be 20nm to 150nm, for example, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 110nm, 120nm, 130nm, 140nm, etc., or in any range of the above arbitrary values. When the thickness of the first coating layer is too thin, the possibility of its rupture / deep damage during the use of the positive electrode active material will increase, resulting in a significant reduction in the effect of improving and protecting the performance of the first positive electrode active material; when the thickness of the first coating layer is too thick, lithium ions need a longer transmission path to reach the active material system from the electrolyte, which has a greater impact on the performance of the active material. In addition, when the coating layer is sintered, the coating material will react with the lithium in the internal material, resulting in a reduction in the available active lithium in the material, and the corresponding material gram capacity is reduced. In this application, by controlling the thickness of the first coating layer within the above given range, the above problems can be effectively avoided or reduced, and the rate performance of the first positive electrode active material can be effectively improved, and the surface structure of the material can be stabilized. At the same time, based on the Dv50 particle size of the first positive electrode active material, by controlling the thickness of the first coating layer within a given range, it is also beneficial to further enable the composite positive electrode to obtain a high energy density.

[0080] In some embodiments of the present application, a second coating layer may be provided on the surface of the second positive electrode active material. The provision of the second coating layer can not only prevent the second positive electrode active material from contacting with the electrolyte, thereby reducing the side reaction between the second positive electrode active material and the electrolyte, but also avoid or inhibit the dissolution of transition metals or doping elements in the second positive electrode active material, while improving its structural stability, thereby improving the cycle stability and safety of the positive electrode active material. Optionally, the second coating layer may include at least one of pyrophosphate, phosphate and carbon. Among them, metal ions are difficult to migrate in pyrophosphate, and selecting pyrophosphate as the coating layer material can effectively isolate the metal ions doped in the positive electrode material from the electrolyte; further, the pyrophosphate can be selected as a crystalline pyrophosphate, and the structure of the crystalline pyrophosphate is stable. As a coating layer material, it is beneficial to effectively inhibit the dissolution of transition metals in the active material and improve the cycle performance. Phosphate coating can improve the ion transport performance of the positive electrode material, which is conducive to promoting the transmission of lithium ions; further, the phosphate can be a crystalline phosphate. The crystalline phosphate and the crystalline pyrophosphate have a high lattice matching degree, good stability and excellent lithium ion conductivity. Using them to coat the second positive electrode active material can improve the stability of the positive electrode active material, effectively reduce the interface side reactions of the electrolyte, and thus improve the high-temperature cycle and storage performance of the battery. Carbon coating can effectively improve the conductivity and desolvation ability of the positive electrode active material. Carbon materials have good electronic conductivity. When used in batteries, electrochemical reactions occur, which require the participation of electrons. In order to increase the electron transmission between particles and the electron transmission at different positions of particles, carbon with excellent conductivity can be used to coat the positive electrode active material. It can be understood that when the second coating layer includes pyrophosphate, phosphate and carbon at the same time, the pyrophosphate, phosphate and carbon can be located in the same coating layer or in at least two sub-coating layers. For example, a pyrophosphate coating layer, a phosphate coating layer and a carbon coating layer can be formed in sequence on the surface of the second positive electrode active material, or a phosphate coating layer, a pyrophosphate coating layer and a carbon coating layer can be formed in sequence on the surface of the second positive electrode active material. Or, a composite coating layer of pyrophosphate and phosphate can be first formed on the surface of the second positive electrode active material, and then a carbon coating layer can be formed on the surface of the composite coating layer.

[0081] In some embodiments of the present application, the thickness of the second coating layer may be 10 nm to 50 nm. For example, it may be 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, etc., or within any range of the above-mentioned arbitrary values. Controlling the thickness of the second coating layer within the given range can not only effectively hinder the dissolution of transition metals or doping elements in the second positive electrode active material, and reduce the lattice change rate of the second positive electrode active material, but also avoid the coating thickness being too large to affect the migration of lithium ions and the energy density of the battery, thereby further improving the battery's kinetic performance, cycle performance and safety without sacrificing the gram capacity of the second positive electrode active material.

[0082] As a specific example, the second coating layer may include a first sub-coating layer, a second sub-coating layer and a third sub-coating layer, the first sub-coating layer may coat the second positive electrode active material and include crystalline pyrophosphate, the second sub-coating layer may include crystalline phosphate and coat the first sub-coating layer, and the third sub-coating layer may be carbon and coat the second sub-coating layer. Pyrophosphate as the first sub-coating layer can effectively isolate the metal ions doped in the second positive electrode active material from the electrolyte, and the crystalline pyrophosphate coating is conducive to effectively inhibiting the dissolution of transition metals in the second positive electrode active material and improving the cycle performance; the crystalline phosphate as the second sub-coating layer has a high lattice matching degree with the crystalline pyrophosphate in the first sub-coating layer, and has better stability than pyrophosphate and has excellent lithium ion conductivity, which is conducive to improving the stability of the positive electrode active material and reducing the interface side reaction between the positive electrode active material and the electrolyte; the third sub-coating layer can enhance the electron transport between particles, improve the electronic conductivity of the positive electrode active material, and effectively improve the conductivity and desolvation ability of the positive electrode active material. Further, the thickness of the first sub-coating layer can be 1nm to 10nm, such as 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, etc., or within any range of the above-mentioned arbitrary numerical values. When the thickness of the first sub-coating layer is within the given range, it is beneficial to avoid the adverse effect on the kinetic properties of the positive electrode active material that may be caused when it is too thick, and it is beneficial to avoid the problem that the migration of transition metal ions may not be effectively hindered when it is too thin; the thickness of the second sub-coating layer can be 2nm to 15nm, such as 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 11nm, 12nm, 13nm, 14nm, etc., or within any range of the above-mentioned arbitrary numerical values. The thickness of the second sub-coating layer is too large and may cause Affects the platform voltage of the overall positive electrode active material. When the thickness of the second sub-coating layer is within the given range, its surface structure is stable and the side reaction with the electrolyte is small, which is beneficial to effectively reduce the interface side reaction, thereby improving the high temperature cycle performance and high temperature storage performance of the battery; the thickness of the third sub-coating layer can be 2nm to 25nm, such as 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm, 22nm, 24nm, etc., or within any range of any of the above values. When the thickness of the third sub-coating layer is within the given range, it is beneficial to improve the conductivity of the positive electrode active material and improve the compaction density of the positive electrode sheet, while avoiding the problem of affecting the compaction density of the sheet due to excessive coating thickness when the sub-coating layer contains amorphous carbon.

[0083] Among them, in the present application, the thickness test of each coating layer can be carried out by FIB, and the specific method may include the following steps: randomly selecting a single particle from the positive electrode active material powder to be tested, cutting a thin slice with a thickness of about 100nm from the middle position or near the middle position of the selected particle, and then performing TEM testing on the thin slice, measuring the thickness of the coating layer, measuring 3 to 5 positions, and taking the average value.

[0084] The second aspect of the present application provides a secondary battery, which includes: the positive electrode sheet of the first aspect of the present application.

[0085] In a secondary battery, a shell assembly, a positive electrode sheet, a negative electrode sheet, a diaphragm, and an electrolyte are generally included. The positive electrode sheet, the negative electrode sheet, the diaphragm, and the electrolyte are located in a receiving cavity formed by the shell assembly. According to the type of battery, the shell assembly may be an aluminum-plastic film or a metal shell assembly, etc. The metal shell assembly may include a square shell assembly and a cylindrical shell assembly. When the shell assembly is a metal shell assembly, it generally includes a shell having an opening on at least one side and a cover for sealing the opening. Regardless of the type of battery, as long as its positive electrode sheet includes the positive electrode sheet of the first aspect of the present application, it can be understood as being included in the technical scope of the battery of the fourth aspect of the present application. In addition to the characteristics such as the compaction density of the active material and the active material layer of the aforementioned part of the positive electrode sheet, other structural features or material selection of the positive electrode sheet, as well as the selection of the negative electrode sheet, the diaphragm, and the electrolyte, can adopt conventional selections in the art, and those skilled in the art can flexibly select according to actual needs.

[0086] In some embodiments of the present application, the secondary battery can be either a laminated battery or a wound battery, and the wound battery can be either a square battery or a cylindrical battery. Optionally, the battery can be a cylindrical battery. Depending on the type of battery, the positive electrode sheet, the negative electrode sheet and the separator can be stacked to form a laminated unit, or can be stacked and then wound to form a wound body.

[0087] In some embodiments of the present application, the battery may be a single cell or a battery module assembled from cells. The battery module may include multiple cells, and the specific number may be adjusted according to the application and capacity of the battery module. Furthermore, the battery module may also include a packaging assembly with a receiving space, and the packaging assembly may include a bottom plate, a side plate, a cover plate, etc.

[0088] In some embodiments of the present application, the above-mentioned battery modules may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.

[0089] In addition, the present application also provides an electrical device, which includes: the positive electrode sheet of the first aspect of the present application, and / or the secondary battery of the second aspect of the present application.

[0090] The secondary battery, such as a battery cell, a battery module or a battery pack, can be used as a power source for the electrical device or as an energy storage unit for the electrical device. The electrical device may include, but is not limited to, mobile devices (such as mobile phones, laptop computers), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, and energy storage systems. As a specific example, the electrical device may be a vehicle.

[0091] The electrical device can select the specific type of battery according to its usage requirements, such as battery cells, battery modules or battery packs.

[0092] As an example, the electric device may be a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. In order to meet the electric device's requirements for high power and high energy density of the battery, a battery pack or a battery module may be used.

[0093] As another example, the electrical device may be a mobile phone, a tablet computer, or a laptop computer. The electrical device is usually required to be thin and light, and may use a battery cell as a power source.

[0094] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0095] Preparation and testing methods of secondary batteries:

[0096] 1. Soft-pack laminated battery:

[0097] ① Preparation of positive electrode sheet:

[0098] The positive electrode active material, polyvinylidene fluoride (PVDF) and conductive carbon are added to a certain amount of N-methylpyrrolidone (NMP), and the mass ratio of the positive electrode active material: polyvinylidene fluoride: conductive carbon is 90:5:5. The mixture is stirred in a drying room to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·S. The slurry is coated on an aluminum foil and dried to form a positive electrode sheet.

[0099] ② Preparation of negative electrode sheet:

[0100] Graphite, sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), and conductive carbon are added to a certain amount of deionized water, with the mass ratio of graphite: sodium carboxymethyl cellulose: styrene butadiene rubber: conductive carbon being 90:2:3:5, and stirred to form a uniform slurry with a viscosity controlled at 3000-10000 mPa·S. The slurry is coated on a copper foil and dried to form a negative electrode sheet.

[0101] ③ Preparation of soft-pack laminated batteries:

[0102] The prepared positive electrode sheet, negative electrode sheet and separator (polyethylene (PE) porous polymer film) are made into corresponding battery cells according to the Z-shaped stacking structure, and the battery cells are vacuum dried at 90°C for 12 hours, and then the positive and negative electrode tabs are ultrasonically welded. The positive electrode uses an aluminum tab and the negative electrode uses a nickel tab. The positive and negative electrode tabs are located on the same side of the battery cell. The battery cell after the tab welding is loaded into an aluminum-plastic film of a suitable size for top-side packaging. The conventional packaging temperature is 145°C, and the electrolyte is injected (the electrolyte is 1mol / LLiPF6 / (ethylene carbonate (EC)+diethyl carbonate (DEC)+dimethyl carbonate (DMC)) (volume ratio 1:1:1)+5wt.% fluoroethylene carbonate (FEC)), let it stand, form, age, exhaust, double seal, and capacity test to obtain the prepared soft-pack stacked battery.

[0103] 2. Carry out cycle test on the prepared soft-pack laminated battery at 25°C:

[0104] The prepared soft-pack laminated battery was charged to 4.4V at 0.5C0 at 2.5-4.4V in a constant temperature environment of 25°C, then charged at a constant voltage at 4.4V until the current was ≤0.05C0, left to stand for 5 minutes, and then discharged to 2.5V at 1C0. The capacity was recorded as C n (n=1,2,3……), repeat the above operation, the capacity retention rate is calculated according to C n / C3 ratio calculation, when C n / C3×100%=80%, extract the corresponding number of cycles as the evaluation index of cycle capacity;

[0105] 3. Positive electrode film resistance test:

[0106] The diaphragm resistance is tested using a BER1300 diaphragm resistance meter. The test steps are as follows: (a) prepare the electrode into a disc with a diameter of 22 mm; (b) place the prepared disc on the test platform of the BER1300 instrument; (c) adjust the machine test pressure to 0.4 T, the test temperature to 25 ° C, and the test time to 10 s, and then start the test. The obtained resistance value is the diaphragm resistance.

[0107] 4. 10%~80% SOC charging time experiment:

[0108] First, the capacity of the soft-pack laminated battery is tested. The process is as follows: 0.33C constant current charging to the full charge voltage V1 is switched to constant voltage charging. When the charging current is reduced to 0.05C, the constant voltage charging ends. Then 0.33C discharge is performed to the full discharge voltage V2. This process is repeated 3 times, and the third capacity result is taken as the basis. At the same time, the third result can be used to calculate the positive electrode gram capacity.

[0109] The soft-pack laminated battery was subjected to different rates (C1 <C2<C3<C4<……<C n ) Charging test, the charging rate needs to be from small to large during the test, and the full voltage of the soft-pack laminated battery and the negative electrode voltage of the soft-pack laminated battery need to be monitored simultaneously during the charging process. The detailed process is as follows: the soft-pack laminated battery is charged to the full charge voltage V1 or the negative electrode voltage is 0V according to C1, the battery SOC value at the end of charging is extracted, and then 0.33C is discharged to the full discharge voltage V2, and the above process is repeated to obtain the SOC value at the end of charging at different rates. The SOC-rate at the end of charging is made into a scatter plot, and the relationship between the SOC and the rate at the end of charging is fitted. 20%, 30%, 40%, 50%, 60%, 70%, 80% are substituted into the relationship to obtain the corresponding rate (C 20% , C 30% , C 40% , C 50% , C 60% , C 70% , C 80% ) can be used to calculate the 10% to 80% SOC charging time, 10% to 80% SOC charging time = (60 / C 20% +60 / C 30% +……+60 / C 80% )×10%.

[0110] Example 1

[0111] In soft pack laminated batteries:

[0112] (i) Positive electrode sheet: The number of layers of the positive electrode sheet is 15; the thickness of a single-layer positive electrode sheet is 0.13 mm; the weight of the positive electrode active material layer per unit area of ​​the positive electrode sheet is 0.038 g / cm 2 The first positive electrode active material is NCM523, the Dv50 particle size of the first positive electrode active material is 4.2 μm, and the specific surface area of ​​the first positive electrode active material is 0.5 m 2 / g; the second positive electrode active material is LiMn 0.6 Fe 0.4 PO4, the Dv50 particle size of the second positive electrode active material is 0.8 μm, and the specific surface area of ​​the second positive electrode active material is 13.3 m 2 / g; the positive electrode meets: A′ is Fe, The electrode resistance is 0.7Ω.

[0113] (ii) Negative electrode sheet: The number of negative electrode sheets is 16; the thickness of a single-layer negative electrode sheet is 0.13 mm; the weight of the negative electrode active material layer per unit area of ​​the negative electrode sheet is 0.012 to 0.030 g / cm 2 .

[0114] (iii) Diaphragm: The number of diaphragm layers is 16; the thickness of a single-layer diaphragm is 0.012 mm.

[0115] (iv) The inner thickness of the battery case is 6.1 mm.

[0116] (v) The filling coefficient of the secondary battery is 2.84 g / Ah.

[0117] Examples 2 to 15 and Comparative Examples 1 to 3

[0118] The difference between Examples 1 to 9 and Comparative Examples 1 to 3 and Example 1 is that: The value range of is different, and this difference is achieved by changing the blending ratio of the first positive electrode active material and the second positive electrode active material, as shown in Table 1 for details.

[0119] The difference between Examples 10 to 15 and Example 1 is that the types of the second positive electrode active material are different, see Table 1 for details.

[0120] The batteries assembled in Examples 1 to 15 and Comparative Examples 1 to 3 were tested. The test results are shown in Table 1.

[0121] Table 1 Differences between Examples 1 to 15 and Comparative Examples 1 to 3 and related test results

[0122]

[0123]

[0124] Results and Conclusions:

[0125] In combination with the above embodiments and comparative examples, it can be seen that the battery design scheme of the present application can improve the fast charging performance and cycle performance of the battery. Specifically, in combination with embodiments 1 to 9 and comparative examples 1 to 3, it can be seen that when the first positive electrode active material and the second positive electrode active material are determined, as the mixing ratio of the two changes, the resistance of the positive electrode sheet, the content of the Mn element in the electrode sheet, and the relative amount of the Mn element and the A' element (the Fe element in the above embodiment), and The value of will change accordingly; Combining Example 1 and Examples 10 to 15, it can be seen that the change in the type of the second positive electrode active material will also affect the resistance of the positive electrode sheet, the content of the Mn element in the electrode sheet, and the relative amount of the Mn element and the A' element (the Fe element in the above embodiment), and But in general, When the value range of is between 0.002 and 0.2, the fast charging performance and cycle performance of the battery are relatively good, and it can be selected as 0.03 to 0.085; on this basis, the relative amount of Mn and Fe in the positive electrode sheet The value of can be selected from 3 to 20, and further selected from 5 to 17.

[0126] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.

Claims

1. A positive electrode sheet, characterized in that: The positive electrode sheet includes a positive electrode active material layer, wherein the positive electrode active material layer includes a first positive electrode active material and a second positive electrode active material. The first positive electrode active material includes Li a Ni b Co c M 1d M 2e O f R′ g , where 0.75 ≤ a ≤ 1.2, 0 < b < 1, 0 < c < 1, 0 < d < 1, 0 ≤ e ≤ 0.2, 1 ≤ f ≤ 2.5, 0 ≤ g ≤ 1, f + g ≤ 3, M1 is Mn element and / or Al element, M2 includes one or more elements of Zr, Zn, Cu, Cr, Mg, Fe, V, Ti, Sr, Sb, Y, W, Nb, etc., and R′ includes one or more elements of N, F, S, Cl, etc.; The second positive electrode active material includes Li 1+x M 3n Mn 1-y A′ y P 1-z E z O4, wherein -0.100≤x≤0.100, 0≤n≤1.1, 0.001≤y≤0.500, 0≤z≤0.100, M3 includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Nb, Mo and W, A′ includes one or more elements selected from the group consisting of Zn, Al, Na, K, Mg, Mo, W, Ti, V, Zr, Fe, Ga, Sn, Sb, Nb and Ge, and E includes one or more elements selected from the group consisting of B, Si, N, S, F, Cl and Br; The positive electrode sheet satisfies: 0.01≤w (A′) ≤0.05;0.032≤T≤0.043;0.11≤d≤0.16;0.1≤R≤1; in: w (Mn) is the mass fraction of Mn in the positive electrode active material layer; w (A′) is the mass fraction of A′ in the positive electrode active material layer; d is the thickness of the positive electrode active material layer, in mm; T is the weight of the positive electrode active material layer per unit area of ​​the positive electrode sheet, in g / cm 2 ; R is the resistance of the positive electrode sheet at 25° C., in Ω.

2. The positive electrode sheet according to claim 1, characterized in that: Optionally, Among them, w (A′) is the mass fraction of A′ in the positive electrode active material layer, w (P) is the mass fraction of P in the positive electrode active material layer.

3. The positive electrode sheet according to claim 1 or 2, characterized in that: The second positive electrode active material includes at least one of the following two positive electrode active materials: (i) 0.001≤y≤0.500, n=0, the second positive electrode active material is Li 1+x Mn 1-y A′ y P 1-z E z O4; (ii) 0.001≤y≤0.500, 0.9≤n≤1.1, and the second positive electrode active material is Li 1+x M 3n Mn 1-y A′ y P 1- z E z O4, Optionally, the second positive electrode active material is: (ii) Li 1+x Mn 1-y A′ y P 1-z E z O4.

4. The positive electrode sheet according to any one of claims 1 to 3, characterized in that: 0.035≤T≤0.039。 5. The positive electrode sheet according to any one of claims 1 to 4, characterized in that: 0.12≤d≤0.14。 6. The positive electrode sheet according to any one of claims 1 to 5, characterized in that: M1 is a Mn element.

7. The positive electrode sheet according to any one of claims 1 to 6, characterized in that: At least one of the following conditions is met: Alternatively, The Dv50 particle size of the second positive electrode active material is 0.21 μm to 1.53 μm, optionally 0.32 μm to 1.4 μm, further optionally 0.41 μm to 1.25 μm, further optionally 0.38 μm to 1.1 μm, and further optionally 0.47 μm to 0.91 μm; The specific surface area of ​​the second positive electrode active material is 9.2 m 2 / g~23.6m 2 / g, optional 10.5m 2 / g~19.6m 2 / g, and can be selected as 12.0m 2 / g~16.2m 2 / g, 10.0m can also be selected 2 / g~21.5m 2 / g, and can be selected as 10.9m 2 / g~17.6m 2 / g.

8. The positive electrode sheet according to claim 7, characterized in that: Optionally, 9. The positive electrode sheet according to any one of claims 1 to 8, characterized in that: The Dv50 particle size of the first positive electrode active material is 2.1 μm to 6.3 μm, and can be optionally 3.5 μm to 4.9 μm.

10. The positive electrode sheet according to any one of claims 1 to 9, characterized in that: The specific surface area of ​​the first positive electrode active material is 0.3 m 2 / g~1.2m 2 / g, optional 0.5m 2 / g~0.9m 2 / g.

11. The positive electrode sheet according to any one of claims 1 to 10, characterized in that: A first coating layer is provided on the surface of the first positive electrode active material. Optionally, the first coating layer includes one or more elements selected from the group consisting of Ti, Al, B, Nb, Zr, Si and W.

12. The positive electrode sheet according to claim 11, characterized in that: The thickness of the first coating layer is 20 nm to 150 nm.

13. The positive electrode sheet according to any one of claims 1 to 12, characterized in that: A second coating layer is provided on the surface of the second positive electrode active material. Optionally, the second coating layer includes at least one of pyrophosphate, phosphate and carbon.

14. The positive electrode sheet according to claim 13, characterized in that: The thickness of the second coating layer is 10 nm to 50 nm.

15. The positive electrode sheet according to any one of claims 1 to 14, characterized in that: In the second positive electrode active material, E includes one or more elements selected from the group consisting of B, Si, N and S.

16. The positive electrode sheet according to any one of claims 1 to 15, characterized in that: In the second positive electrode active material, A′ includes one or more elements selected from the group consisting of Fe, Ti, V, Ni, Co and Mg.

17. A secondary battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 16.

18. An electrical device, characterized in that: A secondary battery comprising the positive electrode sheet according to any one of claims 1 to 16 and / or the secondary battery according to claim 17.

Citation Information

Patent Citations

  • Lithium ion secondary battery and anode sheet thereof

    CN102427123A

  • Electrochemical device and electronic device

    CN115336067A

  • Method and apparatus for predicting potential accidents and controlling actions to avoid potential accidents for agricultural machinery performing autonomous driving and operating a PTO in a communication system

    KR102458856B1

  • Positive electrode active material for non-aqueous electrolyte secondary battery

    US20090050841A1